Influence of fetal acidemia on fetal heart rate analyzed by computerized cardiotocography in pregnancies with placental insufficiency. (December 2013) - Maeda, Mariane de Fátima Y.; Nomura, Roseli M. Y.; Niigaki, Juliana I.; Francisco, Rossana P. V.; Zugaib, Marcelo
Abstract Objective: To determine the influence of fetal acidemia on fetal heart rate (FHR) parameters analyzed by computerized cardiotocography (cCTG) in pregnancies with placental insufficiency. Methods: This was a cross-sectional study of 46 pregnancies with placental insufficiency between 26 and 34 weeks gestation by abnormal umbilical artery Doppler [pulsatility index (PI) > 95th percentile]. Results: Twenty fetuses had acidemia at birth, pH < 7.20 (43.5%) and 26 had normal pH (56.5%). In the analysis of FHR parameters, fetal movements (FM) per hour was significantly lower in the group with acidemia (median = 2) when compared with the group with normal pH (median = 15, p = 0.019). The values of pH correlated positively with FM (ρ = 0.35; p = 0.019, 95% CI: 0.061 to 0.577) and basal FHR (ρ = 0.37, p = 0, 011, 95% CI: 0.090 to 0.597) and negatively with the ductus venosus (DV) PI for veins (PIV) z-score (ρ = −0.31, p = 0, 036, 95% CI: −0.550 to −0.021). Logistic regression showed that the DV PIV z-score (p = 0.0232) and basal FHR (p = 0.0401) were independent variables associated with acidemia at birth. Conclusions: The present results suggest that cCTG parameters may be useful in the management of cases with early onset placental insufficiency in association with Doppler velocimetry assessment, and that basal FHR and DV-PIV are most clearly in association with acidemia at birth.